2023
DOI: 10.1021/acs.est.2c07656
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Urinary Phthalate Metabolites with Thyroid Function and the Mediated Role of Cytokines: A Panel Study of Healthy Children

Abstract: Evidence on joint association of a phthalate mixture with thyroid function among children and its underlying mechanism is largely unknown. We aimed to explore the associations of 10 urinary phthalate metabolites (mPAEs), either as individuals or as a mixture, with thyroid function indicators [free thyroxine, free triiodothyronine (FT3), and thyroid-stimulating hormone (TSH)] in 144 children aged 4–12 years with up to 3 repeated visits across 3 seasons. Significant and positive associations were observed for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Regarding phthalate metabolites, mono- n -butyl phthalate (MnBP) has been linked to a decline in TSH levels (Figure a), , and associated with an increase in TT4, TT3, and FT3 (Figures c, S2, and S3). Similarly, monobenzyl phthalate (MBzP) has been found to lead to an increase in FT3 levels in children (Figure c) . Phthalates, such as diethyl phthalate, can also strongly interact with blood TTR. ,, …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Regarding phthalate metabolites, mono- n -butyl phthalate (MnBP) has been linked to a decline in TSH levels (Figure a), , and associated with an increase in TT4, TT3, and FT3 (Figures c, S2, and S3). Similarly, monobenzyl phthalate (MBzP) has been found to lead to an increase in FT3 levels in children (Figure c) . Phthalates, such as diethyl phthalate, can also strongly interact with blood TTR. ,, …”
Section: Discussionmentioning
confidence: 96%
“…229 Similarly, monobenzyl phthalate (MBzP) has been found to lead to an increase in FT3 levels in children (Figure 7c). 230 Phthalates, such as diethyl phthalate, can also strongly interact with blood TTR. 193,194,231 In general, chemicals tend to competitively bind with TTR and TRs, leading to an increase in FTHs levels in circulation.…”
Section: Hyperthyroidism Risk Chemicalsmentioning
confidence: 99%
“…5 A study of urine samples from children showed a significant correlation between MEHP and elevated thyroidstimulating hormone (TSH). 6 Additionally, another study of urine from preschool children found a significant correlation between MEHP and free triiodothyronine (FT3). 7 Several potential mechanisms exist for the disruption of the TH homeostasis by phthalates.…”
Section: Introductionmentioning
confidence: 99%
“…Current research suggests that the MEHP level may be associated with the homeostasis of the THs . A study of urine samples from children showed a significant correlation between MEHP and elevated thyroid-stimulating hormone (TSH) . Additionally, another study of urine from preschool children found a significant correlation between MEHP and free triiodothyronine (FT3) .…”
Section: Introductionmentioning
confidence: 99%
“…Phthalic acid esters (PAEs) are extensively utilized as plasticizers and easily migrate into the natural environment, resulting in presentation everywhere. , To make matters worse, some PAEs, including dibutyl phthalate (DBP) and di­(2-ethylhexyl) phthalate (DEHP), have been identified as endocrine disruptors that threaten ecosystem function and human health. , Notably, DBP and DEHP are two frequently detected carcinogenic environmental toxins in human body fluids , and have been involved in the priority pollutant list of the United States Environmental Protection Agency (U.S. EPA) and the European Union (EU) . Till now, methods for PAEs determination mainly include gas chromatography-tandem mass spectrometry (GC-MS/MS), gas chromatography (GC), liquid chromatography-mass spectrometry (LC-MS/MS), and high-performance liquid chromatography .…”
Section: Introductionmentioning
confidence: 99%